2019
DOI: 10.4149/neo_2018_171227n845
|View full text |Cite
|
Sign up to set email alerts
|

TCF19 enhances cell proliferation in hepatocellular carcinoma by activating the ATK/FOXO1 signaling pathway

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal malignancies because of its complexity, high metastasis, recurrence and limited treatment options. Reports state that transcription factor 19 (TCF19) is related to the susceptibility to chronic HBV infection and that it strongly increases the risk of HCC occurrence, but its molecular mechanisms remain unknown. This study analyzed the datasets and confirmed that TCF19 is significantly increased in HCC cell lines and tissues. MTT and colony formation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…37 Subsequently, we demonstrated that miR-1207-5p directly inhibited the expression of TCF19, a newly identified target of miR-1207-5p, that could play an oncogenic role in several cancers, such as colorectal cancer, 23 non-small cell lung cancer, 24 and liver cancer. 22,38 Consistent with the findings of previous studies, 22,38 we demonstrated that TCF19 promoted cell proliferation in HCC. Besides, we further showed the migratory capacities of liver cancer cells regulated by TCF19.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…37 Subsequently, we demonstrated that miR-1207-5p directly inhibited the expression of TCF19, a newly identified target of miR-1207-5p, that could play an oncogenic role in several cancers, such as colorectal cancer, 23 non-small cell lung cancer, 24 and liver cancer. 22,38 Consistent with the findings of previous studies, 22,38 we demonstrated that TCF19 promoted cell proliferation in HCC. Besides, we further showed the migratory capacities of liver cancer cells regulated by TCF19.…”
Section: Discussionsupporting
confidence: 92%
“…[22][23][24] Herein, we also demonstrated that TCF19 promoted cell proliferation in liver cancer by MTT assay and colony formation assay ( Figure 6A-C), which was consistent with the demonstrations in the previous report. 22 However, whether TCF19 also affected the migration and invasion abilities of liver cancer cells was unreported. Therefore, we measured the migration and invasion of liver cancer cells by altering the expression of TCF19.…”
Section: Tcf19 Promoted the Proliferation And Metastasis Of Liver Cansupporting
confidence: 91%
See 1 more Smart Citation
“…There were no reports of the expression level of THBD in brain tumors, our study showed that THBD was highly expressed in GBM patients, and patients with different expression levels had inequable prognosis. Finally, several studies had found that in non-small cell lung cancer, hepatocellular carcinoma, and colorectal cancer TCF19 (transcription factor 19) could promote cell proliferation and increase tumor invasiveness through some pathways, but there were no reports about its role in GBM [33][34][35][36]. Our study found that TCF19 was highly expressed in GBM patients, and patients with different expression levels also had inequable prognosis.…”
Section: Discussionmentioning
confidence: 54%
“…SNP in tumor suppressor RAD54L is important for the development of pancreatic cancer [176], but this polymorphic gene may be identified with the development of BRCA. Genes, such as CDCA3 [177], KIF15 [178], and TCF19 [179], are linked with the proliferation of various cancer cells, such as oral cancer, pancreatic cancer, and hepatocellular carcinoma cells, but these genes may be responsible for the proliferation of BRCA cells. Genes, such as BOP1 [180], KIF11 [181], and MMS22L [182], are associated with the progression of various cancers, such as colorectal cancer, gastric cancer, lung, and esophageal cancer, but these genes may be linked with the development of BRCA.…”
Section: Discussionmentioning
confidence: 99%